Influence of the measuring tools on the flow characteristics in vortex chamber pump - Rogovyi, A. S.; Neskorozhenyi, A. O.; Роговий, А. С.; Нескорожений, А. О. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. Perturbation of the flow by measuring instruments forces researchers to choose optical research methods. But these methods significantly increase the cost of experimental research, due to the high cost of optical-type measuring equipment. On the other hand, using contact methods for measuring the flow velocity, such as Pitot tubes, hot-wire anemometers, the researcher must be sure that the measurement results can really be compared with the calculations results and the equipment influence on the flow parameters is minimal. The aim of this work is to study the measuring tool influence on the flow characteristics in the swirl chamber pump, as well as to compare the results obtained due to the measurements with the parameters of the undisturbed flow. The research methodology consisted of two stages: 1) modeling the flow in the model pump; 2) comparison of flow characteristics, as well as the values of velocity and pressure at the points of installation of the measuring tool. Results. Although the total velocity at the measuring point is practically independent of the measuring tool, the tangential component of the velocity is significantly reduced. It indicates that there is a significant error in velocity measuring. For a more accurate rotational velocity component measurement, it is necessary to orient the instrument perpendicular to the measured component. Scientific novelty. Installing the measuring tool in the end cover of the swirl chamber reduces the flow rate sucked by the pump through the lower axial channel. The size of the tool has practically no effect on the energy characteristics of the swirl chamber pump. Practical value. To ensure measurement accuracy, the ratio of the swirl chamber dimensions and the tool should be ensured in the way that the relative diameter of the tool does not exceed 0.25 of the swirl chamber neck diameter.
Вплив вимірювального інструменту на характеристики течії у вихорокамерному насосі
Keywords: swirl chamber pump; velocity measurement; instrument; numerical simulation; flow patterns; вихорокамерний насос; вимірювання швидкості; інструмент; чисельне моделювання; 621.22:621.694; 10.30977/AT.2219-8342.2021.48.0.86